Gender Differences in the Context of Obstructive Sleep Apnea and Metabolic Diseases - Martins, Fátima O.; Conde, Sílvia V. (Frontiers in Physiology, 2021)
The relationship between obstructive sleep apnea (OSA) and endocrine and metabolic disease is unequivocal. OSA, that is characterized by intermittent hypoxia and sleep fragmentation, leads to, and exacerbates obesity, metabolic syndrome and type 2 diabetes (T2D) as well as endocrine disturbances, as hypothyroidism and Cushing syndrome, among others. However, this relationship is bidirectional with endocrine and metabolic diseases being considered major risk factors for the development of OSA. For example, polycystic ovary syndrome (PCOS), one of the most common endocrine disorders in women at reproductive age, is significantly associated with OSA in adult patients. Several factors have been postulated to contribute/or being in the genesis of dysmetabolic states in OSA these including the increase in sympathetic activation, the deregulation of the hypothalamus-pituitary axis, the generation of reactive oxygen species (ROS), insulin resistance, alteration in adipokines levels and inflammation of the adipose tissue. However, probably the alterations in the hypothalamus-pituitary axis and the altered secretion of hormones from the peripheral endocrine glands would play a major role on the gender differences in the link OSA-dysmetabolism. In fact, normal sleep is different between men and women due to the physiologic differences between genders, with sex hormones, such as progesterone, androgens, and estrogens, being also connected with breathing pathologies. Moreover, it is very well known that OSA is more prevalent among men than women, however the prevalence in women increases after menopause. At the same time, the step-rise in obesity and its comorbidities go along with mounting evidence of clinically important sex and gender differences. Metabolic and cardiovascular diseases, seen as a men's illness for decades, presently are more common in women than in men and obesity has a higher association to insulin-resistance related risk factors in women than in men. In this way, in the present manuscript, we will review the major findings on the overall mechanisms that connect OSA and dysmetabolism giving special attention to the specific regulation of this relationship in each gender. We will also detail the gender-specific effects of hormone replacement therapies on metabolic control and sleep apnea.